MODERN RESEARCH METHODS FOR SUSPECTED BREAST CANCER (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The high incidence of diseases of the mammary glands is considered one of the most the main factors that have a significant impact on the health status of women. Number of new cases of breast cancer detected annuall in various countries of the world, today the period has exceeded 1 million and is 10% of all malignant tumors of various localizations. Despite the successes in treatment and the increase in the diagnostic capabilities of this pathology, the mortality rate from breast cancer remains significant. This is primarily due to the late diagnosis of this pathology in conjunction with the untimely recruitment of patients, andIn addition, there is a lack of highly sensitive methods for determining the early stages of breast cancer, and insufficient clear diagnosis of metastases to regional lymph nodes